Laryngeal mask airway indications: new frontiers for second-generation supraglottic airways. Issue 6 (December 2015) - Timmermann, Arnd; Bergner, Urs Adrian; Russo, Sebastian Giuseppe
Abstract : Purpose of review: Because of the many advantages of supraglottic airways (SGA) compared to mask ventilation and endotracheal intubation, their areas of application are constantly expanding. The development of second-generation SGAs in particular has led to a widening of the indications for use thanks to the improved oropharyngeal leak pressure and the possibility of inserting a gastric tube. The identification of possible malpositions and any increased ventilation requirements using simple clinical tests must be given particular emphasis. The question of patient safety for expanded indications has to be evaluated. Recent findings: The review describes the evolution of these devices in detail with an analysis of the increased range of possible uses for prolonged application periods, minor laparoscopic procedures, obese patients, surgery in the prone position, and caesarean sections. Summary: The use of second-generation SGA for expanded indications seems useful and safe, provided the contraindications are heeded, the placement and performance tests are successfully completed and there is adequate clinical expertise.